Growth and fur characteristics of blue foxes (Alopex lagopus) fed diets with different protein levels and with or without DL-methionine supplementation in the growing-furring period - Dahlman, Tuula; Valaja, Jarmo; Jalava, Taina; Skrede, A. (Agricultural Institute of Canada, 2003)
v 2003 ok